Kontribusi Minat Baca Terhadap Keterampilan Pemahaman Membaca Siswa - Reflinda, Reflinda (LITERATUS, 2024)
Interest in reading is one of the factors that determines students’ reading comprehension. This study aims to reveal the influence of reading interest on the reading comprehension of students in the FTIK UIN Bukittinggi English Study Program for the 2022/2023 academic year. This study utilized a correlational descriptive design with a quantitative approach. Research data were collected using Likert scale questionnaires. The research data were analyzed using simple linear regression. The results of the analysis showed that reading interest contributed to the reading comprehension of students in the English Study Program, Faculty of Tarbiyah UIN Bukittinggi by 10.6%. The better the students' reading interest, the better their comprehension in reading. Additionally, this study highlights the importance of fostering a strong reading culture among students to enhance their academic performance and overall understanding of the material. Encouraging reading interest can lead to significant improvements in reading comprehension skills, benefiting their academic success.